Juridical Analysis of Build Operate Transfer Agreements at the Mataram Mall Building - Septina Indi Huwaida; Zainal Asikin; Eduardus Bayo Sili (International Journal of Integrated Science and Technology, 2024)
The purpose of this research is to identify and analyze the regulation of Build Operate Transfer (BOT) agreements in positive law in Indonesia and the legal issues in the BOT agreement between the Mataram City Government and PT Pacifik Cilinaya Fantacy. The research method used is normative legal research with a legislative approach and a conceptual approach. The types of data used include secondary and primary data. Secondary data consists of literature sourced from primary, secondary, and tertiary legal materials. The regulation of Build Operate Transfer is essentially the same as general contract regulations, which are governed by the third book of the Civil Code regarding obligations. Additionally, Build Operate Transfer is also regulated by several other regulations, including: Government Regulation No. 27 of 2014, Presidential Regulation No. 13 of 2010, Minister of Finance Regulation No. 78/PMK.06/2014, and Minister of Finance Regulation No. 02/PMK.06/2008 concerning the Appraisal of State-Owned Assets. The legal issue in this Build Operate Transfer agreement is that PT Pacifik Cilinaya Fantacy failed to comply with and PT Pacifik Cilinaya Fantacy regarding the management of the APHM Cilinaya Area. PT Pacifik Cilinaya Fantacy did not fulfill its obligation to pay royalties to the Mataram City Government from 2016 to 2019.